The Impact of Smartphone Use on Student Learning Motivation in the 21st Century - Sati Sati; Gitta Ayulissa Grahana; Fitri Meliani (Edumaspul: Jurnal Pendidikan, 2023)
The smartphone is a cellular phone using various services such as memory, screen, microprocessor, and built-in modem, so the features on this smartphone are very complete compared to mobile phone features. This study aims to see the impact of using smartphone in the learning process of elementary school students. This study used qualitative descriptive method. Based on the results of observations, interviews, and questionnaires in grade V SD Negeri 1 Kebonturi, Arjawinangun District, Cirebon Regency, there are negative impacts on smartphone use. This is shown by students experiencing decreased concentration, laziness, and the effects of opium. It is expected that teachers are able to give direction to their students about the negative effects of smartphone use, able to give directions that using smartphones must be with awareness of the time where and when to use a good smartphone.